Preparation and Use of Photocatalytically Active Segmented Ag|ZnO and Coaxial TiO(2)-Ag Nanowires Made by Templated Electrodeposition - Maijenburg, A. Wouter (MyJove Corporation, 2014)
Photocatalytically active nanostructures require a large specific surface area with the presence of many catalytically active sites for the oxidation and reduction half reactions, and fast electron (hole) diffusion and charge separation. Nanowires present suitable architectures to meet these requirements. Axially segmented Ag|ZnO and radially segmented (coaxial) TiO(2)-Ag nanowires with a diameter of 200 nm and a length of 6-20 µm were made by templated electrodeposition within the pores of polycarbonate track-etched (PCTE) or anodized aluminum oxide (AAO) membranes, respectively. In the photocatalytic experiments, the ZnO and TiO(2) phases acted as photoanodes, and Ag as cathode. No external circuit is needed to connect both electrodes, which is a key advantage over conventional photo-electrochemical cells. For making segmented Ag|ZnO nanowires, the Ag salt electrolyte was replaced after formation of the Ag segment to form a ZnO segment attached to the Ag segment. For making coaxial TiO(2)-Ag nanowires, a TiO(2) gel was first formed by the electrochemically induced sol-gel method. Drying and thermal annealing of the as-formed TiO(2) gel resulted in the formation of crystalline TiO(2) nanotubes. A subsequent Ag electrodeposition step inside the TiO(2) nanotubes resulted in formation of coaxial TiO(2)-Ag nanowires. Due to the combination of an n-type semiconductor (ZnO or TiO(2)) and a metal (Ag) within the same nanowire, a Schottky barrier was created at the interface between the phases. To demonstrate the photocatalytic activity of these nanowires, the Ag|ZnO nanowires were used in a photocatalytic experiment in which H(2) gas was detected upon UV illumination of the nanowires dispersed in a methanol/water mixture. After 17 min of illumination, approximately 0.2 vol% H(2) gas was detected from a suspension of ~0.1 g of Ag|ZnO nanowires in a 50 ml 80 vol% aqueous methanol solution.